2008
DOI: 10.1097/ede.0b013e318169cc87
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity of Children to Swimming-Associated Gastrointestinal Illness

Abstract: Measurement of the indicator bacteria Enterococci in recreational water using a rapid QPCR method predicted swimming-associated GI illness at freshwater beaches polluted by sewage discharge. Children at 10 years or younger were at greater risk for GI illness following exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
215
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(227 citation statements)
references
References 25 publications
8
215
2
2
Order By: Relevance
“…In addition, the designed primerprobe set for ENT has high specificity for Enterococcus faecium and Enterococcus faecalis, which are abundant in animal gastrointestinal tracts, whereas the culture-based method is less specific and may grow nonenteric species that occur naturally in the environment, such as Enterococcus casseliflavus (37). Studies have also suggested that qPCR results are more capable of predicting gastrointestinal illness than culture-based results (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the designed primerprobe set for ENT has high specificity for Enterococcus faecium and Enterococcus faecalis, which are abundant in animal gastrointestinal tracts, whereas the culture-based method is less specific and may grow nonenteric species that occur naturally in the environment, such as Enterococcus casseliflavus (37). Studies have also suggested that qPCR results are more capable of predicting gastrointestinal illness than culture-based results (38).…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli (E. coli), enterococci, Campylobacter, Salmonella) indicative of fecal pollution have been recovered in Cladophora mats, with counts of E. coli and enterococci often exceeding 100,000 CFU/g dry weight (Byappanahalli et al 2003a;Ksoll et al 2007;Ishii et al 2006a;Englebert et al 2008b). The U.S. Environmental Protection Agency (EPA) established recreational water quality criteria based on epidemiological studies linking E. coli concentrations to gastroenteritis illness in swimmers using doi: 10.2166/wst.2010.230 Great Lakes beaches (U.S. EPA 1986; Wade et al 2008). Kleinheinz & Englebert (2005) suggest the risk associated with E. coli washing out of mats may not be the same as with E. coli presumably originating from anthropogenic sources (e.g.…”
Section: The Majority Of These Investigations Have Addressedmentioning
confidence: 99%
“…S. aureus is commonly detected at recreational beaches in both seawater and sand (32)(33)(34)(35)(36), suggesting that the recreational water environment may be an important reservoir for S. aureus. Epidemiology studies have found associations between recreational water contact and skin ailments (37)(38)(39)(40), further pointing to recreational water exposure as a transmission route for pathogenic S. aureus.…”
mentioning
confidence: 99%